PELATIHAN PENGOLAHAN KULIT MELINJO SEBAGAI CAMILAN SEHAT UNTUK PENINGKATAN PENDAPATAN KWT SEJAHTERA DUSUN KEPUH KULON DESA WIROKERTEN - Anis Febri Nilansari; Setia Wardani (Institut Teknologi Dirgantara Adisutjipto, 2021)
The partner on Community Devotion (PkM) is a group of farmer Women (KWT) Sejahtera who is engaged in agriculture, located in the hamlet of Dusun Kepuh Kulon Desa Wirokerten is 10.7 km from PGRI Yogyakarta University (UPY). The main problem with the partners is the abundance of residual products from KWT Sejahtera, which is a skin that has not been managed and utilized by members and communities to increase family income because there is no assistance on the processing of snacks, local market reach and the design and packaging of the products are still conventional. The purpose of PkM raised the awareness of KWT Sejahtera Dusun Kepuh Kulon Desa Wirokerten in the use of Melinjo skin, providing experience and knowledge of Melinjo skin treatment, the price determination of Melinjo skin and product packaging as well as sales of social media-assisted products. Solutions to address the problems that exist in the partner is by counseling and training methods such as (1) Counseling and skin treatment training Melinjo, (2) Training on product packaging, (3) Product marketing management training by utilizing social media. The results of this PkM are Melinjo skin chips that have been packaged, the promotion of products by utilizing social media as well as articles published on the Journal of Community Devotion.